2010
DOI: 10.1097/nmd.0b013e3181e07d3d
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Behavior and Early Maladaptive Schemas in Subgroups of Eating Disorders

Abstract: To examine relationship between Eating Disorder Behaviors (EDB) and Early Maladaptive Schemas (EMS) across eating disorder (ED) subgroups. EMS and ED behaviors were measured by Young Schema Questionnaire and Eating Behavior Severity Scale, respectively, among patients diagnosed with Restrictive or Binge/purging Anorexia, or bulimia nervosa. Canonical component analysis showed significant association between ED behaviors and EMSs. Canonical factor-pairs (EDB and EMS) revealed specific associations between certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
5
35
0
2
Order By: Relevance
“…Interestingly, for the ED participants, whilst ED related worries emerged at the surface level, broader psychopathological issues such as fear of rejection or abandonment, fear of being negatively judged by others, and feelings of personal inadequacy, emerged as themes that evolved over the course of catastrophizing. This lends support to the idea that ED pathology typically is linked to wider intra-and interpersonal difficulties (Rieger et al, 2010;Schmidt & Treasure, 2006;Sternheim et al, 2011;Unoka, Tolgyes, Czobor, & Simon, 2010;Zachrisson & Skarderud, 2010) and that the process of catastrophizing enables the elaboration of these deep seated concerns.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, for the ED participants, whilst ED related worries emerged at the surface level, broader psychopathological issues such as fear of rejection or abandonment, fear of being negatively judged by others, and feelings of personal inadequacy, emerged as themes that evolved over the course of catastrophizing. This lends support to the idea that ED pathology typically is linked to wider intra-and interpersonal difficulties (Rieger et al, 2010;Schmidt & Treasure, 2006;Sternheim et al, 2011;Unoka, Tolgyes, Czobor, & Simon, 2010;Zachrisson & Skarderud, 2010) and that the process of catastrophizing enables the elaboration of these deep seated concerns.…”
Section: Discussionsupporting
confidence: 61%
“…Fourteen employed Young's Schema Questionnaire (YSQ; Young, 1994); only six of these met criteria for a meta-analysis (see Appendix A for references & Table 2). Data from two studies by Unoka and colleagues were pooled without repetition to avoid overlap as some participants appeared in both publications (Unoka, Tolgyes, & Czobor, 2007;Unoka, Tolgyes, Czobor, & Simon, 2010). YSQ measures early maladaptive schemata across broad categories pertaining to early attachment experiences: emotional deprivation, abandonment/instability, mistrust/abuse, social isolation, dependence/incompetence, harm-vulnerability, enmeshment, defectiveness/shame, failure to achieve, subjugation, emotional inhibition, self-sacrifice, unrelenting standards, entitlement/grandiosity, insufficient self-control and fear of losing control.…”
Section: Beliefs and Schematamentioning
confidence: 99%
“…For example, Jones and colleagues (2007) reviewed the literature on dysfunctional core beliefs among individuals with EDs and found that bulimic behaviors are associated with all 18 EMS, while purging behaviors have been associated with the abandonment, defectiveness, social isolation, failure, self-sacrifice, and emotional inhibition schemas. Similarly, Unoka and colleagues (2010) examined the relationship between EMS and ED behaviors and found that eating behaviors resulting in immediate rewards (e.g., bingeing, purging, and use of diet pills) was positively associated with the abandonment, emotional inhibition, enmeshment, emotional deprivation, and subjugation schemas.…”
Section: Ems and Edsmentioning
confidence: 99%